PENILAIAN FAKTOR-FAKTOR MAKRO EKONOMI, COUPON, YIELD TO MATURITY, TIME TO MATURITY DAN RATING TERHADAP FAIR PRICE SUKUK KORPORASI PASAR MODAL SYARIAH DI INDONESIA PERIODE TAHUN 2014-2018 - Teni Rubiyanti (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
Capital Market with sharia principles in Indonesia has several regulations that regulate the use of Fair Prices in corporate sukuk instruments. Fair price is used as a reference in transactions as well as provisions in the presentation of Financial Statements for Financial Institutions and Investment Managers related to Mutual Fund products. The research aims to examine the effect of macroeconomic factors (Inflation, SBIS Yield Rate, Profit Sharing Rate of Mudharabah Deposits, Rupiah Exchange Rate to Dollar), Coupon Rate, Yield to Maturity, Time to Maturity, and Ratings partially and simultaneously to Fair Price Corporate Sukuk for the period 2014-2018. The source of research data is taken from several institutions which are statistical and historical data of transactions, which consist of BI, OJK, IDX, IBPA, KSEI and PEFINDO. This research is a quantitative approach, where sampling is done by purposive sampling consisting of 7 corporate sukuk series. The analysis technique uses the Panel Data Regression Test with a random effect model and hypothesis testing using t-statistics, testing the coefficient of determination, and F-statistics to test the effect of variables together with a significance level of 5%. The results showed that the Rupiah to Dollar Exchange Rate, Coupon Rate, and Time to Maturity had a positive and significant effect, Yield to Maturity had a negative and significant effect while Inflation, SBIS Yield Rate, and Profit Sharing Rate of Mudharabah Deposits did not significantly influence the Fair Price of Corporate Sukuk, but simultaneously all of these variables significantly influence the Fair Price of Corporate Sukuk. For testing the coefficient of determination obtained by 86.49% shows the ability of the independent variable in explaining the Corporate Fair Price Fair, the remaining 13.51% is explained by other variables not included in this study.